Foto Bonaudi - Chapter 4 - Tarrio, Gustavo (Conjuro, 2006)
Verzio FF Submission The fourth episode of a documentary series that tells the story of a family of photographers from Santa Fe, New Mexico. This episode looks at the relationship between the Bonaudis and the town of Sunchales. The numerous interviews with the locals, including teachers, the mayor and other photographers, reveal the ties between the Bonaudis, photography and the city. Although many of the people are satisfied with Bonaudi’s work, it proves insufficient to assure the future of the studio.